Analisis Kepuasan Orang Tua Anak Autism Terhadap Pelayanan Fisioterapi Di Klinik Mitra Insan Mandiri Ponorogo - Devi Ayu Trisnaningrum; Fransisca Xaveria Hargiani; Wahyu Teja Kusuma; Nurul Halimah (Jurnal Keperawatan Muhammadiyah, 2022)
Objectives : Autism is one part of the type of children with special needs. In an area, it is hoped that there will be many health facilities that can accommodate services that can be accessed by the community for handling children with autism. Every parent wants optimal service in a service for the good of their children. The purpose of this study was to analyze the level of satisfaction of parents of autism patients with the service system, the level of satisfaction of parents of autism patients with physiotherapy measures, the level of satisfaction of parents of autism patients with facilities within the scope of physiotherapy services at Mitra Insan Mandiri Clinic, Ponorogo. Methods : This research was conducted by distributing questionnaires to parents of children with autism and filled in directly through the google form and the data analysis process with descriptive analysis calculations as a whole was carried out with the help of the SPSS (Statistical Package for Social Sciences) program. This study to assess the level of patient satisfaction required instruments in the form of validity and reliability tests. Results : There are satisfactory results for the services provided by the Mitra Insan Mandiri clinic in PonorogoConclusion : It is proven that parents of autism patients are satisfied with the service system at the Mitra Insan Mandiri clinic, Ponorogo.